Carbon Emission Disclosure: Antecedents and Consequences (A Study of Manufacturing Companies in Indonesia Stock Exchange) - Stephen, Hieronimus; Pakiding, Daniel L (AJAR, 2025)
This study aims to analyze the effect of profitability on carbon emission disclosure, analyze the effect of leverage on carbon emission disclosure, analyze the effect of carbon emission disclosure on bid-ask price differences, analyze the effect of carbon emission disclosure on trading volume, analyze the effect of carbon emission disclosure on stock price volatility. This study uses stakeholder theory and signalling theory. This study uses secondary data. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange during the 2020-2023 period. The number of companies that met the sampling criteria was 16 companies with a total sample of 64. The data analysis technique for this study was carried out using the Statistical Package for the Social Sciences (SPSS) software. The results of this study indicate that profitability has a positive and insignificant effect on carbon emission disclosure, leverage has a negative and insignificant effect on carbon emission disclosure, carbon emission disclosure has a negative and significant effect on bid-ask price differences, carbon emission disclosure has a positive and significant effect on trading volume, and carbon emission disclosure has a positive and insignificant effect on stock price volatility.